Determinants of maize farmers market participation in Southern Ethiopia: Emphasis on demographic, socioeconomic and institutional factors - Tafesse, Alula; Gechere, Gezahagn; Asale , Alemayehu; Belay, Abrham; Recha, John W.M.; Aynekulu, Ermias; Berhane, Zerihun; Osano, Philip M.; Demissie, Teferi Dejene; Solomon, Dawit (Informa UK Limited, 2023)
Maize is the main cereal crop that supports the livelihoods of millions of smallholder farmers in Africa. However, one of the main bottlenecks for maize production is low market penetration. This study examined the factors influencing the likelihood of smallholder farmers taking part in maize trading in southern Ethiopia using cross-sectional data collected from 360 smallholder maize growers. The data were examined with inferential statistics and the Heckman two-stage sample selection econometric model. Household head age and sex, maize price, household size, farm experience, market distance, access to transportation, frequency of extension contact, land size, amount of credit received, market information, and off-farm income were all found to be significant factors that determine maize farmers’ market participation. Investment in road infrastructure in maize production potential areas and access to market information is mainly needed to increase maize trading.